Empowerment and resistence : A study of women refugees as members of self-organized groups in UK - Khan, Mohammad Moniruzzaman; Khan, Sanzida (BRAC University, 2010)
In relation to the theoretical and empirical construction of my research this study focuses on refugee and asylum seeker women as members of self organized groups and how these have contributed to women’s empowerment and the debate surrounding gender interests and women’s political mobilization. To do this research, qualitative methodology was conducted using semi structured interview technique to gain in-depth data from the four refugees/asylum seekers from different countries. A positive impact of belonging to a collective movement for women asylum seekers and refugees has been found in this study. Because they have found a space for resistance and empowerment by organizing collectively around their specific needs. This research has also shown that ethnicity and gender are clearly very important factors in creating and maintaining group solidarity amongst the women.